Analyzing the role of non-seasonal discounts in consumer expenses for a small market environment (International Journal of Scientific Research and Management (IJSRM), 2018)
Here we consider the observed changes in the consumer expenses in a district of Albania following market sales discount. By calculating latent variable as the usefulness of the discounts offered we interpret the net expenses surplus as related to the actual marketing activities. Here we use a reduced set of variables related to the house holding as gender and age of principal buyers, and some few marketing aspects as telephone calls, whereas as response variable we choose the average days of market visits and expenses. In the area we investigated we obtained that the offered discounts promote rising expenses which in turn tells that the consumer behave as minimalist buyer as a responses of higher prices and not limited budged. This supports the idea that the consumers in this area are mostly rational. Next we see that the most accented effect is related to the average costume expenses that suggest the marketing activity related to this category of consumers.